The Frontal Assessment Battery (FAB) effectively discriminates between MCI and dementia within the clinical spectrum of neurochemically confirmed Alzheimer’s disease - Aiello, Edoardo Nicolò; Verde, Federico; Milone, Ilaria; Giacopuzzi Grigoli, Eleonora; Dubini, Antonella; Carelli, Laura; Ferrucci, Roberta; Priori, Alberto; Ratti, Antonia; Torresani, Erminio; Ticozzi, Nicola; Silani, Vincenzo; et al. (Frontiers in Psychology, 2022)
Background This study aimed at testing the ability of the frontal assessment battery (FAB) to differentiate between patients with mild cognitive impairment (MCI) and dementia due to Alzheimer’s disease (AD), as well as comparing its discriminative power to that of the Mini-Mental State Examination (MMSE). Methods The present retrospective cohort included N = 107 Aβ-positive patients diagnosed with either MCI due to AD (N = 40) or probable AD dementia (ADD; N = 67). A two-step multiple logistic regression (MLR) was run to predict an MCI vs. ADD diagnosis based on FAB scores. Within the baseline step, demographics, disease duration, MMSE scores, and information on cognitive phenotypes were entered, with the FAB being added within the second step. Receiver-operating characteristics analyses were also run to derive intrinsic and post-test diagnostics. Results Within the baseline MLR step, only lower MMSE scores predicted the occurrence of ADD; by adding the FAB, which likewise was able to discriminate between MCI and ADD (p = 0.016), a significant increase in model fit was detected (p = 0.007). The diagnostic efficiency of the FAB (AUC = 0.85) was comparable (p = 0.583) to that of the MMSE (AUC = 0.82), also yielding good intrinsic and post-test diagnostics, which were comparable to those of the MMSE. Discussion The FAB is a diagnostically sound screener to discriminate between MCI and ADD, independently of patients’ overall cognitive profile. In doing so, the FAB is comparable to the MMSE, and the complementation of the latter with the former is advisable in order to increase the accuracy in differentiating between MCI and ADD within screening sessions.